Potential of business-to-business electronic commerce in the electronic industry in Singapore. - Tan, Kok Chuan. (2008)
The objective of this research paper is to study the potential of business-to-business electronic commerce in the electronics industry in Singapore. This paper hopes to at the same time identify whether the same factors that have been researched upon have a similar impact on the electronics industry in Singapore.